Komunikasi Persuasif Fasilitator Poli Jiwa dalam Menghapus Tradisi Pasung ODGJ di Madura - Apriliana, Devita; Wahyuningsih, Sri (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: to identify persuasive communication of psychiatric clinic facilitators in eradicating the tradition of pasung PWMD in MaduraMethods: This article uses qualitative research with a case study approach. The data collection technique is purposive sampling, with data collection techniques in the form of observation, interviews, documentation, and audiovisual media. The data analysis technique in this study uses four stages: category collection, direct interpretation, pattern formation, and naturalistic generalization. Informants in this study were mental poly facilitators at the Kokop Bangkalan District Health Center and mental poly facilitators at the Omben Sampang District Health Center.Results: The results showed a significant decrease in cases of PWMD in pasung. In Kokop Subdistrict, Bangkalan in 2018 there were 41 cases. After being treated by the facilitator of the psychiatric clinic of the Kokop Bangkalan Subdistrict Health Center in 2024, the number of PWMD in pasung became 17 people. In Omben Sampang Subdistrict in 2013 there were 54 cases of PWMD in pasung. After being handled by the mental clinic facilitator at the Omben Sampang Subdistrict Health Center, by 2024 the number of PWMD in pasung became 7 people.Conclusion: The process of handling PWMD in pasung at the Kokop Bangkalan Subdistrict Health Center and Omben Sampang Subdistrict Health Center requires trust and a good relationship with the family, the surrounding community and the PWMD in pasung. . The psychiatric clinic facilitator carries out the persuasive communication process by paying attention to the credibility of the source of information, the message or content of the message, and the ultimate goal of changing the attitude of the family, community, and the ODGJ pasung patient.